Human Hemangioblast-Derived Mesenchymal Stem Cells Promote Islet Engraftment in a Minimal Islet Mass Transplantation Model in Mice - Bertera, Suzanne; Knoll, Michael F.; Knoll, Carmela; Hara, Hidetaka; Kimbrel, Erin A.; Kouris, Nickolas A.; Lanza, Robert; Philips, Brett E.; Garciafigueroa, Yesica; Giannoukakis, Nick; Cooper, David K. C.; Trucco, Massimo; et al. (Frontiers in Medicine, 2021)
Islet transplantation can restore glycemic control in patients with type 1 diabetes. Using this procedure, the early stages of engraftment are often crucial to long-term islet function, and outcomes are not always successful. Numerous studies have shown that mesenchymal stem cells (MSCs) facilitate islet graft function. However, experimental data can be inconsistent due to variables associated with MSC generation (including donor characteristics and tissue source), thus, demonstrating the need for a well-characterized and uniform cell product before translation to the clinic. Unlike bone marrow- or adipose tissue-derived MSCs, human embryonic stem cell-derived-MSCs (hESC-MSCs) offer an unlimited source of stable and highly-characterized cells that are easily scalable. Here, we studied the effects of human hemangioblast-derived mesenchymal cells (HMCs), (ie: MSCs differentiated from hESCs using a hemangioblast intermediate), on islet cell transplantation using a minimal islet mass model. The co-transplantation of the HMCs allowed a mass of islets that was insufficient to correct diabetes on its own to restore glycemic control in all recipients. Our in vitro studies help to elucidate the mechanisms including reduction of cytokine stress by which the HMCs support islet graft protection in vivo. Derivation, stability, and scalability of the HMC source may offer unique advantages for clinical applications, including fewer islets needed for successful islet transplantation.